Endocannabinoid System as a Promising Therapeutic Target in Inflammatory Bowel Disease – A Systematic Review - Hryhorowicz, Szymon; Kaczmarek-Ryś, Marta; Zielińska, Aleksandra; Scott, Rodney J.; Słomski, Ryszard; Pławski, Andrzej (Frontiers in Immunology, 2021)
Inflammatory bowel disease (IBD) is a general term used to describe a group of chronic inflammatory conditions of the gastrointestinal tract of unknown etiology, including two main forms: Crohn's disease (CD) and ulcerative colitis (UC). The endocannabinoid system (ECS) plays an important role in modulating many physiological processes including intestinal homeostasis, modulation of gastrointestinal motility, visceral sensation, or immunomodulation of inflammation in IBD. It consists of cannabinoid receptors (CB1 and CB2), transporters for cellular uptake of endocannabinoid ligands, endogenous bioactive lipids (Anandamide and 2-arachidonoylglycerol), and the enzymes responsible for their synthesis and degradation (fatty acid amide hydrolase and monoacylglycerol lipase), the manipulation of which through agonists and antagonists of the system, shows a potential therapeutic role for ECS in inflammatory bowel disease. In this review, we summarize the role of ECS components on intestinal inflammation suggesting the advantages of cannabinoid-based therapies in inflammatory bowel disease.